Social Network and Family Business Internationalization in South Eastern Nigeria - Agbim, Kenneth Chukwujioke; Eluka, Johnny (Journal of Accounting, Business and Finance Research, 2018)
Social network relationships through social associations, clubs and social networking platforms are known to facilitate family business internationalization. However, this has not been empirically brought to the fore with respect to the family businesses in Nigeria. Owing to the commonplaceness of social networks and family businesses in South Eastern Nigeria and their involvement in cross border business, this study seeks to examine the effect of social network on the internationalization of family businesses in the zone. The study adopted survey design. Proportionate stratified random sampling and simple random sampling techniques were employed to determine the sample size. The generated data via questionnaire were analyzed using linear regression. The results show that the effect of social network on family business internationalization is significant and positive. The study therefore lends itself as a veritable empirical evidence and support to the Uppsala Internationalization Process Model. To promote cross border business, the researchers recommends the sensitization of family business founder/CEOs or descendant/CEOs on the need to belong to both national and international social associations. This social relationship has the potential of: fostering in founder/CEOs the use of social network platforms for communication; exposing the founder/CEOs to international business knowledge/experience; and linking founder/CEOs to foreign partners, investors, funds, facilities and markets.